Raising Helen - Hoberman, David; Amritraj, Ashok; Amiel, Jack.; Begler, Michael; Marshall, Garry; Hudson, Kate, 1979-; Corbett, John, 1961-; Cusack, Joan, 1962-; Panettiere, Hayden, 1989-; Breslin, Spencer; Breslin, Abigail, 1996-; Mirren, Helen; et al. (United States] Touchstone Home Entertainment Burbank, CA Distributed by Buena Vista Home Entertainment, 2004)
Helen is living the life she's always dreamed of with her career at a top modeling agency on the rise. But her carefree lifestyle comes to a crashing halt when she soon finds herself responsible for her sister's children - Audrey, Henry, and Sarah. No one doubts that Helen is the coolest aunt in New York, but the transformation from super-hip to super-mom is super difficult. Along the way, Helen finds support from Dan Parker, the handsome young pastor and principal of the kids' new school, and realizes the choice she has to make is between the life she's always loved and the new loves of her life.
Special features: bloopers from the set; deleted scenes; Liz Phair "Extraordinary" music video; audio commentary with director Garry Marshall and the writers.
Director of photography, Charles Minsky ; editors, Bruce Green, Tara Timpone ; music, John Debney ; costume designer, Gary Jones ; production designer, Steven Jordan.
Kate Hudson, John Corbett, Joan Cusack, Hayden Panettiere, Spencer Breslin, Abigail Breslin, Helen Mirren.
MPAA rating: PG-13; for thematic issues involving teens.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital, DTS, SDDS.
English or dubbed French dialogue, French or Spanish subtitles; closed-captioned.
Keywords: Aunts -- New York (State) -- New York -- Drama; Guardian and ward -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama